EFFECTS OF UREA MOLASSES MINERAL BLOCK MIXED WITH HERBS ON GROWTH PERFORMANCE, PARASITIC REDUCTION AND COST PRODUCTION IN GOATS - Hattakum, Chonnapat; Sawanon, Suriya; Jeeraphun, Thatree (Life Sciences and Environment Journal, 2017)
The concentrate supplementation of urea molasses mineral block (UMMB) is a technology that enhances nutrient and mixing herbs to reduce parasitic number in rearing ruminant animals. In this experiment, goat hybrid native - Anglo Nubian weaned that had average weight of 16.36±1.16 kilograms. A total of 20 goats were randomly divided into 5 groups, 4 goats in a group arranged in a completely randomized design. Group 1 was fed without UMMB supplementation, group 2 was supplemented with UMMB, group 3 was supplemented with UMMB mixed Combretum quadrangulare, group 4 was supplemented with UMMB mixed Cucurbita moschata and group 5 was supplemented with UMMB mixed Tamarindus indica. All goats were individually housed in pens for 4 months. The results found that the supplementation UMMB in group 2, 3, 4 and 5 provided significantly different average daily grain (ADG) higher than group 1 (without UMMB supplementation). Especially, group 3 (UMMB mixed Combretum quadrangulare) provided the highest AD Gat 37.33 g/day and group 5 (UMMB mixed Tamarindus indica) with ADG of 33.17 g/day respectively. The supplementation of these UMMB provided higher concentrate of urea nitrogen and glucose in blood. Additionally, the supplementation of UMMB mixed herbs in groups 3, 4 and 5 could reduce the number of parasite, which presented the lower worm egg and Eimeria oocyst than group 2 (UMMB without herb). The cost and profit calculation showed that feeding group 3 (UMMB mixed Combretum quadrangulare) provides the highest net profit.